Improvised design of grease trap for the usage at the food premises - Rusli, Muhammad Haziq; Mohd Arish, Nur Aini; Hamidon, Nuramidah; Hashim, Nor Haslina; Mohd Sari, Kamarul Aini; Saji, Nurdalila (Penerbit UTHM, 2020)
In Malaysia, there are many pollutions that emitted from the industry. Water pollution can be caused by various sectors, one of it is the industrial sector of the food service. The food service industry in Malaysia is growing up every day and they are the major contributor to pollution that was caused by fats, oils, and grease that are highly discharged from food premises. Grease traps are widely used by most restaurants and food processing industries to reduce oil and grease to an acceptable level before it can be discharged to public sewers [1]. Grease traps are a pipeline that traps the food waste before they enter the sanitary sewer system. The food waste is from the fats, oils, and greases and is usually found in kitchen waste water. Normally, the grease traps are located under the sink because the place is usually contributed to fat, oil and grease. Among the alternatives to reduce the emission levels of fats, oil, and grease, the uses of the grease trap is required to filter the wastewater released from the premises [2].